The Effectiveness of Using Interactive Digital Media on Early Childhood Literacy Skills: A Comparative Study in Urban and Rural Early Childhood Education (PAUD) - Widiastuti, Sri; Nursidiq, Fajri (Sekolah Tinggi Agama Islam Kuningan, 2025)
Backround: Early childhood literacy development is increasingly mediated by digital technologies, yet empirical evidence regarding interactive digital media effectiveness across diverse socioeconomic contexts remains limited, particularly concerning urban-rural disparities in implementation quality and learning outcomes.Objective: This study investigated the comparative effectiveness of interactive digital media on early literacy competencies among preschool children in urban and rural early childhood education settings, examining contextual factors mediating differential outcomes.Method: This qualitative study employed a comparative case study design conducted over six months in two purposively selected ECEC institutions (one urban, one rural) serving children aged 4-5 years. Data collection involved classroom observations (60 hours), semi-structured interviews with educators (n=12) and parents (n=24), and document analysis. Thematic analysis identified patterns, themes, and comparative insights across contexts.Findings and Implications: Interactive digital media demonstrated differential effectiveness across contexts and literacy domains. Both settings showed improvements in foundational skills (letter recognition, phonological awareness), with digital interventions narrowing urban-rural achievement gaps by 53-69% in these areas. However, gaps in complex competencies (vocabulary, comprehension) persisted or widened due to differential implementation quality, educator digital competency, and home-school technology continuity. Educator mediation emerged as the most critical factor determining effectiveness, surpassing mere technology access.Conclusion: Digital media can support early literacy development when implemented within supportive ecosystems featuring adequate infrastructure, educator capacity, and family engagement. Realizing equity potential requires comprehensive approaches addressing multiple implementation dimensions rather than device distribution alone.